THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND ANXIETY OF FINAL SEMESTER ANESTHESIOLOGY NURSING STUDENTS - Nia Handayani (Universitas Respati Yogyakarta, 2022)
Health students in the final semester are focused on several activities such as completing final assignments, clinical practice in hospitals and preparing for competency tests. Teaching and learning activities for final semester students often become a burden and cause anxiety. Social support from outside has an important role in overcoming this problem. The purpose of this study is to determine the relationship between social support and anxiety of final semester students of the Anesthesiology Nursing Study Program of the University of Aisyiyah Yogyakarta. The population of this study was the seventh semester students of the Anesthesiology Nursing Study Program of the University of Aisyiyah Yogyakarta, totaling 121 students with a research sample of 95 students who were selected by random sampling technique. Data collection was done utilizing a questionnaire with The Multidimensional Scale of Perceived Social Support instrument for the social support and the Hamilton Anxiety Rating Scale instrument for the level of anxiety. Data analysis was conducted using the technique of rho spearman analysis test. The results of the analysis show that there is a significant relationship between social support and anxiety of the final semester student, with a correlation value of -0.592 and a Sig. of 0.000 (p < 0.05). In addition, the results of the analysis also show that there is a strong relationship between social support and anxiety, and the higher the social support obtained by students, the lower the level of anxiety. Keywords: social support; anxiety; anesthesiology nursing; student